Analisis Pelaksanaan Penilaian pada Pembelajaran Tematik Bermuatan IPS Kelas IV SD Negeri 1 Sekarsuli Bantul - Windi Luqianingrum; Heri Maria Zulfiati (Universitas Sarjanawiyata Tamansiswa, 2020)
This is a qualitative descriptive study which aims to find out the implementation of assessment in social science-thematic earning in fourth grade students of SD Negeri 1 Sekarsuli Bantul. The results of data collected show that: (1) The form of assessment used are cognitive, affective and psychomotor domains. (2) The implementation of assessment on thematic learning with social studies is carried out when learning takes place and outside of learning, (a) The cognitive domain, including written tests including daily tests, PTS and PAS. (b) The affective domain includes observation, self-aseessment and peer-to-peer assessment. (c) The psychomotor domain includes the performance assessment in groups. (3) Supporting factors and obstacles to the implementation of the assessment include, supporting factor include the existence of education and training, training and workshops related to assessment, the existence of assessment tools and instruments that facilitate teachers, and the existence of school facilitates to support assessment. While the inhibiting factors in the complexity of the assessment system. This result in the teacher experiencing difficulties in developing assessment, the state of students who did not support the assessment process, the implementation of social studies content assessment took a long time.